THE USE OF MODERN METHODS IN TEACHING FOREIGN LANGUAGES - Abdirasilova Sarvinoz Ravshan qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: The rapid development of globalization, information technologies, and intercultural communication has significantly increased the importance of foreign language education. Traditional teaching methods are gradually being replaced by modern pedagogical approaches that focus on learner-centered instruction, communicative competence, creativity, and technological integration. This article examines the use of modern methods in teaching foreign languages, including communicative language teaching, task-based learning, project-based learning, blended learning, gamification, and digital technologies. The study analyzes the effectiveness of these approaches in improving learners’ speaking, listening, reading, and writing skills.